Sie sind auf Seite 1von 1

@ @@a@bma

) 2010 -2009 (1

001

)L1 = lim ( 2 x 5 + 4 x 4 6 x5 + 1

)L 2 = lim ( 2 x 3 + 5 x 4 + 1

2 x2 + 5x 3
)
x 0,5
4x2 1
3x 4 2 x9 1
( L 5 = lim
)
x
x2 + 2
x 3 + 27
L 7 = lim
x 3 x + 3
3 x 3 + 4 x 1
( L 9 = lim
)
x 1
x 1

2x 7
L 4 = lim ( 2
)
x 3+
x 5x + 6

( L 3 = lim

2x x
x+ x

x 2 + 2 x + 2 3x

x + 11 3
)
x+2

( L 6 = lim
x 2

x 5x
)
x2 + x
) sin( 3 x
L10 = lim
) x 0 tan( 7 x
( L 8 = lim
x 5

L11 = lim

1 2+ x
) 3
x2
x

( L12 = lim

( L13 = lim

x + 2x 3
x 1

L14 = lim

x +

x +

L15 = lim

x +

x 2 + 2 x + 2 + 3x

x 0+

002

003

1
1

2
[ h( x) = 3 x x 4 ; x [0, 2
h ] [ 0 , 1

1
h( x ) = 1 7
]; x [ ,1
6x + 4
2

(1 ) f ( x [ [ 1 , 0 [ [ 0 , 1 [. [1 , 2

) (

008
5

(2 x 4 x :

1 3
)
(1a 2 :
2 5
( a 3 ) 2 ( 5 b 3 ) 4

a3 b2 ( 4

@. f ( x) = 63xx + 15 :

\ .
2 x 3 + 5 x 4 = 0 :
(3

) ( 09 / 08

x +

010
lim 3 x3 + 2 x (1
+

x4 x
(2
x 8
3

x2 1
x 1

lim 3x + 7 1 128 x 7 (4

(5

lim
x8

x +x
3

42 x 2

x 1

lim

lim 2 x 3 4 x 4 + 2 (6

lim
+

x + 63 4

3 | x | + x2
; x0
| x2 + | x

x 1 3

(8

4 + sin x 2
x +1 1

lim

x+

(7

x 1

= ) F ( x F (0) = 3
) ( 09 / 08

gg ( x) = x3 + 4 1 :

g. Dg = [ 3 4 , + [ :
(1
(2 g . Dg

013

(5 . f ( x) = x3 3 x 2 5 La dichotomie

) ( 04/03

f ( x ) = 2 + 8 x
3

f. D f =] , 2 ] :
(1

[. ]2 , 4
f ( x) = 0
(

(2 f D f . D f

.3< < 4
( ) f (3

J . D f
f
(3

006

@@@@@.

f [ I = [1 , +:

(4 )( x

x 1

x +1

x . J
f

( x) = 3 56 :
(5

(1 f . I
1

) ( 04/03

f . x J

. ]1, 2[ :


( x 1) f ( x) = x 3 :
(6

= ). f ( x

f J I )( x
(2

x 0

(3
g E Dg ). g ( x

c [ ]3 , 4. (4 c) f (c ) = 3 c :

lim

(4 f ] [ 3 , 4 . f (3) = 1

( ) f (3,5

nbi

f 0 ). lim f ( x

012

2 . 1
4 x 3 + 9 x 2 + 9 x + 5 = 0 :
(2

\ x + 3 x + 1 = 3 2 x + 1 :
(3

F . 0

) (

= ) . h( x

1 + sin x 1
, x0
= ) f ( x
:

x
f (0) = 0,5

009

011

(2 f 0 . 1

1
(1 [ ] , +
3

x +

x 0+

x 0

(2 a b f .2

(3

)f ( x) = x E ( x

005

(1 ) lim f ( x ) lim f ( x ) lim f ( x ) . lim f ( x

x2 + x 2
f
x
=
(
)
; x 1

f 1 .
| | x 1
f (1) = 3

004

007

x 1

L16 = lim

x 2 + ax 10
x>2
= ) f ( x
x2
. f (2) = 7
:
f ( x) = bx 28
<
2
x

x2 2 x

x +

x 2 2 x 2 3x + 1

2 1

.f

4
014 [ ]0 , +:
x2

. F ( x) = x + 1 +

) ( 08/07